Change in Gait Deviation Index after anti-tumour necrosis factor-α treatment in individuals with rheumatoid arthritis: a pilot study. (October 2013) - Broström, EW; Esbjörnsson, A-C; Heideken, J von; Larsson, P; Wretenberg, P; Iversen, M
Abstract : Objectives: Anti-tumour necrosis factor-alpha (TNF-α) inhibitors provide fast, effective resolution of rheumatoid arthritis (RA) inflammation. In this study we aimed to quantify the impact of TNF-α treatment on gait dynamics. Method: The sample comprised 16 subjects [11 female, median age 56 (range 48–66) years, median disease duration 9.5 (range 4.6–20.6) years] with RA who met the American College of Rheumatology (ACR) criteria, had lower extremity involvement, did not use walking aids, and had started TNF-α treatment within 1 week of baseline gait analysis. Gait analysis focused on three-dimensional (3D) lower extremity joint kinematics, kinetics, time and distance parameters. The Gait Deviation Index (GDI) and GDI-Kinetic were calculated. Data on gait, disease activity, and physical disability were collected at baseline and at 3.5 months. Results: Following treatment with TNF-α, statistically significant improvements were found in disease activity [using the 28-joint Disease Activity Score based on C-reactive protein (DAS28-CRP); median difference (md ) = 2.3, p < 0.01], physical disability [Health Assessment Questionnaire (HAQ) md = 0.4, p < 0.01], and pain during walking [visual analogue scale (VAS) md = 11.0, p < 0.05]. Reductions in gait deviations were noted (GDI md = 3.7, p = 0.04; GDI-Kinetic md = 4.1, p = 0.05) along with reductions in dimensionless time and distance parameters. A moderate to good negative correlation existed between baseline GDI and GDI change scores (rs = –0.7, p < 0.01). Conclusions: Treatment with TNF-α improved gait dynamics in adults with RA. Significant gait deviations were, however, still present after treatment. In this study, GDI and GDI-Kinetic scores appeared to be useful outcome measures to quantify changes in gait deviations after this intervention.